WACANA KEFILSAFATAN DAN MASA DEPAN TRADISI SAINS DALAM ISLAM - Purwadi, Agus (Jurnal Bestari, 1994)
the dichotomy of Islamic thought between traditionalism which gives more emphasis on the aspect of standard doctrine, and rationalism which tends to be open for the whole aspects of science seems being the trigger of hostility of the both sides. Nevertheless, what Moslem should do is developing the philosophy discourses to respond to the increase of western scientific tradition which nota bene has reduced the aspect of trancendental-spiritual that will point to scularism. Furthermore, the following writing serves a responsive alternative for the Islamic thought development, especially, in scientific philosophy field to rearrange the Islamic science tradition which is almost ignored.